2022
DOI: 10.1038/s41598-022-22158-4
|View full text |Cite
|
Sign up to set email alerts
|

Combining NGN2 programming and dopaminergic patterning for a rapid and efficient generation of hiPSC-derived midbrain neurons

Abstract: The use of human derived induced pluripotent stem cells (hiPSCs) differentiated to dopaminergic (DA) neurons offers a valuable experimental model to decorticate the cellular and molecular mechanisms of Parkinson’s disease (PD) pathogenesis. However, the existing approaches present with several limitations, notably the lengthy time course of the protocols and the high variability in the yield of DA neurons. Here we report on the development of an improved approach that combines neurogenin-2 programming with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 83 publications
0
24
0
Order By: Relevance
“…AIW002-02 iPSCs expressing doxycycline-inducible NGN2 were generated as described previously 107 . Briefly, the parental AIW002-02 iPSC line was split with ReLesR (STEMCELL Technologies, 100-0484) and seeded at a density of 135,000 cells per well in a 6-well plate in mTesR1 media plus Y27632 one day prior to simultaneous transduction with separate lentiviruses encoding Ngn2 and rtTA.…”
Section: Methodsmentioning
confidence: 99%
“…AIW002-02 iPSCs expressing doxycycline-inducible NGN2 were generated as described previously 107 . Briefly, the parental AIW002-02 iPSC line was split with ReLesR (STEMCELL Technologies, 100-0484) and seeded at a density of 135,000 cells per well in a 6-well plate in mTesR1 media plus Y27632 one day prior to simultaneous transduction with separate lentiviruses encoding Ngn2 and rtTA.…”
Section: Methodsmentioning
confidence: 99%
“…The following protocol was adopted from Sheta et al [9] to differentiate the iPSCs into iDAs. With an established protocol to generate iPSC-derived cortical neurons (i 3 Ns) [18,22], our i 3 N protocol was combined with the iDA protocol from Sheta et al to modify the media compositions and generate purer populations of iDAs.…”
Section: Ipsc-derived Dopaminergic Neuron Generation Following Sheta ...mentioning
confidence: 99%
“…The versatility of iPSCs has been harnessed in other fields of research, such as cardiac and renal diseases [3,4]. Many groups have embarked on differentiating skin fibroblast-derived iPSCs into dopaminergic neurons, from both healthy and Parkinson's disease affected individuals, using different approaches such as small molecules, transcriptions factors, and microRNAs [1,[5][6][7][8][9][10][11][12][13]. The original protocol published more than a decade ago by Kriks et al [6] used small molecules to generate human dopaminergic neurons from iPSCs, however, the protocol took more than two months to achieve mature human dopaminergic neurons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyphenols are naturally occurring molecules in plants and fruits that have been studied extensively for their potential therapeutic benefit in a number of diseases, including mild cognitive impairment 16,17 and various neurodegenerative disorders [18][19][20] . Our group and others have shown that polyphenols can alleviate neurotoxicity in preclinical models of PD, including flavonoids (a subclass of polyphenols) such as green tea polyphenols [21][22][23] , anthocyanins (ANC) [24][25][26][27] , and isoflavones [28][29][30] , as well as the phenolic acid derivative curcumin 31 and stilbenes such as resveratrol and oxyresveratrol 24,32 . Polyphenols have been shown to protect against oxidative stress in a variety of disease models by scavenging free radicals and up-regulating endogenous cytoprotective responses 33,34 .…”
Section: Introductionmentioning
confidence: 99%